The profitability of the turn in freestyle swimmers/La rentabilidad del viraje en nadadoras del estilo libre - Jorge Luis Pentón López; Luis Ángel García Vásquez; Luis Alberto González Duarte; Adolfo Cruz Carrera; Armando Marín Rojas (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The research refers to a study of the profitability of the freestyle turning action in school swimmers. The objective of the research was focused on evaluating the temporal characteristics during the action of the turn in swimmers of the 13 and 14 years old category in the province of Sancti Spíritus. For the collection of information, the empirical level methods used were: scientific observation, as well as measurement. Two video cameras, placed in series, and a Sony underwater camera were used. For the temporal analysis, the Kinovea software, ver 0.9.3, was used. The 15 m test was applied to check the profitability of the turn. It was possible to verify a poor effectiveness of this technical element in the freestyle in the swimmers evaluated, which showed, in a generalized way, deficiencies during the impulse phase and the formation of very open angles of the legs that favored a deficit in the use of the power of the legs during the wall push, This aspect helped to decrease the sliding and to begin to perform the exit movements to the surface prematurely, increased the time in general in the execution of the turn, concluding that for the school categories it is appropriate to obtain angles between the ankle, knee and hip joints in the range of 90° and 110° at the moment of initiating the wall push.